Solution of cubic-quintic Duffing oscillators using harmonic balance method - Hosen, Md. Alai; Chowdhury, Md. Sazzad Hossien (2014)
In this study, Harmonic balance Method (HBM) is applied to approximate analytic solutions of strongly nonlinear Duffing oscillators with cubic-quintic nonlinear restoring force. In this paper, the HBM is mainly illustrated by the cubic-quintic Duffing oscillator. Numerical comparisons between the HBM and the exact solutions reveal that the HBM is a promising tool for strongly nonlinear oscillator’s problems.